2012
DOI: 10.1007/s11434-012-5168-1
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of planetary-scale zonal mean wind anomalies and polar oscillations

Abstract: Global atmospheric variables can be physically decomposed into four components: (1) the zonal time averaged climate symmetric component, (2) the time averaged climate asymmetric, (3) the zonal-mean transient symmetric anomaly, and (4) the transient asymmetric anomaly. This study analyzes the relationships between the intra-seasonal and inter-annual variability of planetary scale decomposed zonal and meridional winds in the tropopause, and oscillations such as those from the El Niño-Southern Oscillation (ENSO),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The horizontal distribution of the composite surface pressure anomalies in winter (Figure c) shows that there are significant negative anomalies in the northern Siberian region and the regions from the sea area east of Greenland to the Barents Sea, and the minimum negative anomaly values of the two centres are both less than −5 hPa. In contrast, changes in surface pressure in high latitudes can affect mid‐latitudes via meridional circulation (Qian and Liang, ), and there are significant positive anomalies in the mid‐latitude region (35°–50°N), with three centres in western Europe, the Tibetan Plateau region and the Aleutian region, respectively. According to Jhun and Lee (), variability in the intensity of the East Asian winter monsoon is influenced by both the Siberian high and the Aleutian low.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The horizontal distribution of the composite surface pressure anomalies in winter (Figure c) shows that there are significant negative anomalies in the northern Siberian region and the regions from the sea area east of Greenland to the Barents Sea, and the minimum negative anomaly values of the two centres are both less than −5 hPa. In contrast, changes in surface pressure in high latitudes can affect mid‐latitudes via meridional circulation (Qian and Liang, ), and there are significant positive anomalies in the mid‐latitude region (35°–50°N), with three centres in western Europe, the Tibetan Plateau region and the Aleutian region, respectively. According to Jhun and Lee (), variability in the intensity of the East Asian winter monsoon is influenced by both the Siberian high and the Aleutian low.…”
Section: Resultsmentioning
confidence: 97%
“…Due to the reduction in the pressure gradients between the Siberia High and the Aleutian Low, the winter monsoon in East Asia is weaker. Previous studies have also found that when the Arctic Oscillation is positive, the winter monsoon in East Asia is weak, and temperatures increase across China (Qian and Liang, ). Furthermore, the difference in geopotential height in the upper atmosphere between the high latitudes and mid‐latitudes in Asia is enlarged, and air temperature at upper atmosphere in the Barents Sea and the sea east of Greenland increases, and the atmospheric baroclinicity at high latitudes has changed distinctly.…”
Section: Discussionmentioning
confidence: 99%
“…Anomaly-based approach Similar to the monthly mean variable decomposition done by Peixoto and Oort (1992), a daily mean total variable can be decomposed into four components: zonally mean symmetric and asymmetric climates as well as zonally mean symmetric and asymmetric anomalies (Qian 2012a,b). The poleward propagation of zonally mean symmetric anomalous flow is associated with polar oscillations in intraseasonal and interannual scales, while the asymmetric anomaly is associated with regional oscillations (Qian and Liang 2012). Since both the asymmetric climate and symmetric anomaly are negligible for daily synoptic-scale motions, they later simply decomposed the daily mean or hourly variable into two parts: climate and anomaly for weather analysis and forecasting (same as Fig.…”
Section: E851mentioning
confidence: 99%